(untitled) (Jurnal Bahasa, 2025)
Being multilingual is an advantage. However, the language of a particular ethnic group may become endangered as more speakers gain proficiency in more dominant languages. This study aims at investigating the language use among the Melanau ethnic group in Mukah, Sarawak. The objectives of the study are (1) to identify the language use within family, neighbourhood, religious, and education domains; and (2) to examine the trend of language use across the older, adult, and younger generations of the target community. This quantitative study used questionnaires as the research instrument and Fishman’s (1972) domain analysis framework for data analysis. The respondents comprised of 120 multilingual Melanau individuals residing in Mukah. Findings show that Melanau Mukah language remains the primary choice within family and neighbourhood domains. However, the increased in the degree of formality in religious and educational domains has led to greater use of the Sarawakian Malay Dialect and the Malay language, sidelining Melanau Mukah language. While bahasa Melanau Mukah still holds a stable position in among its speakers, the condition is likely to change in the next few generations following the increasingly widespread use of Sarawak Malay dialect among respondents. Continued use of Melanau Mukah dialect at home is necessary to prevent it from becoming endangered. Future studies should explore the relationship between language use and speaker attitudes and assess fluency levels in the Melanau Mukah language among the younger generation. Keywords: Domain analysis, Melanau, Melanau Mukah language, language use, trend across generations, ethnic language Full text: PDF